Effects of sustained swimming on the red and white muscle transcriptome of rainbow trout (Oncorhynchus mykiss) fed a carbohydrate-rich diet - Magnoni, Leonardo Julián (2013)
Training at sustainable swimming speeds can produce changes in fish skeletal muscle that are important for aquaculture due to their growth-potentiating effects. Such changes may be even more relevant when fish are fed diets containing an increasing proportion of carbohydrates as an energy source. We evaluated the effects of moderate-intensity sustained swimming on the transcriptomic response of red and white muscle in rainbow trout fed a carbohydrate-rich diet using microarray and qPCR. Analysis of the red and white muscle transcriptome in resting or swimming (1.3 body lengths/s) for 30 days revealed significant changes in the expression of a large number of genes (395 and 597, respectively), with a total of 218 differentially expressed genes (DEGs) common for both muscles. A large number of the genes involved in glucose use and energy generation, contraction, development, synthesis and catabolism of proteins were up-regulated in red and white muscle. Additionally, DEGs in both muscles were involved in processes of defense response and apoptosis. Skeletal muscle contraction activates a transcriptional program required for the successful adaptation of both muscles to the changing demands imposed by swimming conditions. Future studies should further clarify the mechanisms involved in the adaptation of both tissues to exercise and assess possible benefits of such conditions for cultured fish.